SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS ATAS PENCATATAN NIKAH PADA KANTOR URUSAN AGAMA KECAMATAN SAJIRA - Ghufroon, Naufal; Yasin, Muhammad; Purnomo, D; Hamizar, Hamizar (JURNAL LENTERA AKUNTANSI, 2023)
This research aims to identify and analyze the cash receipts accounting system for marriage registration implemented at the Office of Religious Affairs (KUA) of Sajira District. As the forefront unit of the Ministry of Religious Affairs in public religious services, KUA handles significant economic transactions involving cash, both receipts and disbursements. The importance of this study stems from the need for consistent accounting systems and procedures to reduce the potential for misuse and prevent cash fraud, which often occurs in various institutions. Therefore, cash receipts are the main focus given the vital importance of accountable budget management. This research utilizes primary and secondary data sources, collected through documentation and interviews with relevant parties. A qualitative descriptive approach is employed as the analytical method, using an inductive reasoning to draw conclusions from field findings. The results indicate that the cash receipts system for marriage registration at KUA Sajira District generally conforms to the concepts and procedures of relevant cash receipts system theories, although potential improvements for strengthening internal control and transparency remain open.